Design for sustainability (D4S) in product development using solidworks software: a case study of redesign a sugar cane extractor machine - Kasmin, Ashari (2014)
The Design for Sustainability (D4S) is a recognized method to produce sustainable product that embrace three main elements: environment, economic and social. However, the emphasization on the D4S is immature among industries in Malaysia. The objectives of this study are to propose a user friendly D4S assessment checklist base on SolidWorks software features and to implement on a case study. Implementation of this study done by established a D4S assessment checklist. The checklist consists of mapping between the sustainability main elements and SolidWorks software. The D4S case study is redesign a Sugar Cane Extractor Machine based on the proposed assessment checklist using Solidworks software. The results of study have shown improvement on all three main elements of sustainability. On the environment element, the redesign SCEM has been designed with less environmental impact than original design as following; Carbon Footprint 17.4%, Total Energy Consumed 19.0%, Air Acidification 16.2% and Water Eutrophication 49.4%. On the economic element, the redesign SCEM has been designed less material and production cost than original design for USD28.00 and USD58.50 respectively. On the social element, the redesign SCEM has been equipped with extra safety cover at exposed area and ergonomics handles to ease pushing, pulling and lifting operation. In conclusion, the D4S study has been done successful with consideration on all three main sustainability.